Thirty-Ninth Annual Homecoming Pope's Chapel United Methodist Church, October 1, 1995 - (:unkn) unknown (Wilkes County, Georgia: Pope's Chapel First Methodist Church)
Thirty-Ninth Annual Homecoming Pope's Chapel United Methodist Church, October 1, 1995. Robert L. Reynolds, Jr., pastor. Event program. Pope's Chapel First Methodist Church. Wilkes County, Georgia. United States.
Thirty-Ninth Annual Homecoming Pope's Chapel United Methodist Church, October 1, 1995
1 electronic document. popes-chapel_program_19951001.pdf. 5 pages. 38084861 bytes (master).
Keywords: Church history; Congregational churches; Homecoming; Methodist Church--Anniversaries, etc.; Methodists; Pope's Chapel United Methodist Church (Wilkes County, Ga.); Programs (Publications); United Methodist Church (U.S.); Wilkes County (Ga.); Georgia; Asbury, Francis; Bamford, Sophia; Bohler, Clarence; Bohler, Eugenia; Boyd, James W.; Bunch, Greg; Bunch, Linda; Cash, M.T.; Chafin, David; Chafin, Elizabeth; Chafin, Malcolm; Combs, Farmer; Faulk, Landis; Fortson, Benjamin Winn; Fortson, Warren; Harris, Lundye; Humphries, Thomas; Landrum, John; Neal, Augustus A.; Norman, Ben; Norman, Horace; Norman, Jimmy; Norman, Wilma B.; Ogilvie, Hannah Rebecca; Pope, Henry; Reynolds, Robert L.; Sale, David; Suttles, Albert; Suttles, Joyce; Suttles, Vic; Wheatley, Elaine; Wheatley, Jimmy; Wiggins, Tom